The Role of Airline Travelers' Pre-Recovery Emotions during the Service Recovery Process - Nikbin, Davoud (Routledge, 2015)
This study examines (1) the relationships between airline travelers’ casual attribution (stability and controllability), pre-recovery emotions, post-recovery emotions, and overall satisfaction; and (2) analyzes the mediating effect of pre-recovery emotions on the relationship between causal attribution and post-recovery emotions. Theoretical hypotheses were derived based on a literature review, and to empirically test the hypotheses, data were collected from 210 airline travelers in Malaysia. These respondents were airline travelers who experienced some service failure and relevant service recovery within the past year. According to the results, the two dimensions of casual attribution both influenced pre-recovery emotions. Pre-recovery emotions were significantly related to positive and negative post-recovery emotions, and post-recovery emotions were significantly related to overall satisfaction. In addition, pre-recovery emotions moderated the relationship between casual attribution and post-recovery emotions. These results have important practical implications.